A 1.25–12.5 Gbps Adaptive CTLE with Asynchronous Statistic Eye-Opening Monitor. (15th November 2018) - Cai, Chen; Zhao, Jian-zhong; Zhou, Yu-mei
Abstract : The equalization of a large attenuation signal and multirate communication in high-speed serial interface is hard to balance. To overcome this difficulty, an adaptive equalization system with optimized eye-opening monitor is proposed. The designed eye-opening monitor is based on the asynchronous statistic eye diagram tracking algorithm, and the eye diagram is obtained by undersampling with the low-speed asynchronous clock. With the eye-opening monitor into the adaptive loop, an adaptive equalization system combined with continuous-time linear equalization (CTLE) is completed. And the inductor peaking technology is used to improve the capacity of compensation. With SMIC 28 nm CMOS process to achieve the overall design, the power consumption and core chip area are 12 mW @ 12.5 Gbps and 0.12 mm 2, respectively. And postsimulation results show that it can offer compensation from 6 to 21 dB for 1.25–12.5 Gbps range of receiving data, which achieves a large range of data rate and channel loss, and its power efficiency is 0.046 pJ/bit/dB for the worst case, which is better than most previous works.